Distrust as a psychological phenomenon - Kravchenko, Viktoriia; Shastko, Iryna (My University, 2021)
Purpose. The article provides a theoretical analysis of the problem of mistrust as a psychological phenomenon that is closely related to trust. Methods. To achieve the purpose of the study, methods of psychosocial approach are used (because mistrust is manifested both internally and externally); subjective approach (because mistrust is an independent psychological phenomenon); system approach (allows to take into account all connections, types, forms, criteria of trust-distrust, as well as determinants, consequences, functions). With the help of these methods the essence of distrust is revealed, which has its own criteria and features. Results. Analysis of domestic and foreign works on the psychological phenomenon of mistrust allows us to consider it as a means of ensuring human existence in the global world. Along with other sciences (philosophy, sociology, culturology, economics), which study trust – distrust, psychology has a number of methodological and technological problems. The connection between self-confidence and trust in the world is investigated. The task of the study is to determine the essence of distrust; to trace the connection between trust in oneself and trust in the world; to expand the notion of distrust as a means of personal security; to study distrust as a personality trait. An important point in the existence of a balance of self-confidence and trust in others is the level of self-reflection (awareness, spirituality), which will provide a person with peace and acceptance in an unknown difficult situation or fear and rejection, which often drives a person to act non-stereotypically or stereotypically. Conclusions. In general, it can be concluded that mistrust can manifest itself in suspicion, jealousy, inner tension, "protection", naivety, conformity, dogmatism, negativism, skepticism, intimophobia, unwillingness to make long-term plans, fear of change, excessive propensity to engage. The existence of a balance of self-confidence and trust in others is the level of self-reflection (awareness, spirituality), which will provide a person with balance and self-efficacy in solving life's problems.

Мета статті – здійснити теоретичний аналіз проблеми недовіри як психологічного феномену, що тісно пов’язаний з довірою. Методи. Для реалізації мети дослідження використано методи психосоціального підходу (оскільки недовіра проявляється як на внутрішньому, так і на зовнішньому рівнях); суб’єктного підходу (оскільки недовіра – самостійний психологічний феномен); системного підходу (дає змогу врахувати всі зв’язки, види, форми, критерії довіри-недовіри, а також детермінанти, наслідки, функції). За допомогою цих методів розкрито сутність недовіри, що має свої критерії та особливості. Результати. Аналіз вітчизняних і зарубіжних студій дав підстави розглядати психологічний феномен недовіри як засіб безпечності існування людини в глобальному світі. Як і інші науки, що досліджують довіру – недовіру (філософія, соціологія, культурологія, економіка), психологія містить низку нерозв’язаних методичних і технологічних проблем. Актуальним вбачається дослідження зв'язку довіри до себе та довіри до світу. Саме тому в цьому дослідженні визначено сутність недовіри; простежено зв’язок довіри до себе й довіри до світу; розширено уявлення про недовіру як засіб безпечності особистості; вивчено недовірливість як особистісну рису. Визначено, що запорукою рівноваги довіри до себе і довіри до інших є наявність певного рівня саморефлексії (усвідомленості, духовності), що забезпечує людині спокій і прийняття в невідомій складній ситуації або ж страх і неприйняття, що часто спонукає людину діяти нестереотипно чи навпаки – шаблонно. Висновки. Отже, недовіра може проявлятися в підозрілості, ревнивості, внутрішній напрузі, «захисті», наївності, конформності, догматизмі, негативізмі, скептицизмі, інтимофобії, небажанні будувати довгострокові плани, страхові змін, надмірній схильності до узагальнень тощо. Важливим моментом в існуванні рівноваги довіри до себе і довіри до інших є рівень саморефлексії, що і забезпечить людині баланс та самоефективність у вирішенні життєвих проблем.
НЕДОВІРА ЯК ПСИХОЛОГІЧНИЙ ФЕНОМЕН
Keywords: Trust; distrust; credulity; safety; danger; 159.953